BOLALARDA BUYRAK TOSH KASALLIKLARI DIAGNOSTIKASI (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
Kidney stone disease in children has become an increasingly significant problem in pediatric nephrology in recent years. The absence or low intensity of clinical symptoms at early stages complicates timely diagnosis and may lead to severe complications if detected late. This scientific work evaluates the effectiveness of clinical, laboratory, and instrumental diagnostic methods used for the detection of kidney stone disease in pediatric patients. The results demonstrate that ultrasonography is the primary screening method, while computed tomography provides high diagnostic accuracy in complicated cases.